Peran dan Manajemen Waktu dalam Penggunaan Smartphone - Nabila Putri Syahrina; Melly Eunike; Farid Wahyu Saputra; Futihah Ananda Khoirusiffa; Azzahra Nadya Khairunnisa; Saskia Dwi Rahmawati; Antonio Amabel Setiawan; Muhammad Sunan Magribi Herlambang; Ravi Islami Adeza; Dwi Desi Yayi Tarina (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The service was carried out at SDN Pulogebang 02 on October 17, 2024 with the theme of the role and time management in the use of smartphones. Smartphones are important for Generation Z, but many do not understand the proper use of smartphones, as well as the inappropriate use of smartphones, this is the problem of our group's research, this research aims to generation Z can understand the role and proper smartphone time management. The method used is to present material about time management in the use of smartphones. The samples in this study were 6B and 6C class students. The techniques used are Post-Test and Pre-Test, as well as doing Ice Breaking to break the atmosphere of the students who are not focused on the material we provide. Data collection techniques using interviews, questionnaires, and documentation. The results of this service show that there is a link between time management and the application of Pancasila values, namely the attitude of discipline towards students of SDN Pulogebang 02. This is shown from the results of interviews that have been conducted with 6th grade students that they have time in the use of playing Smartphone.